Enhanced antibacterial hybrid phase-change porous fiber membrane as well as preparation method and application thereof
The preparation of porous fiber membranes loaded with phase change materials, tannin acid and metal nanoenzymes by electrospinning method solves the problem that traditional wound dressings can easily lead to tissue adhesion and lack of antibacterial function after long-term use, and achieves efficient antibacterial and Wound healing effect.
Patent Information
- Application Number
- CN202411422103.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Existing wound dressings can easily lead to tissue adhesions after long-term use, which may cause wound pain and bleeding when changing dressings. They lack antibacterial and healing functions, making it difficult to effectively deal with bacterial infection wounds.
An electrospinning method was used to prepare a hybrid phase-change porous fiber membrane that enhances antibacteriality. By loading a multi-stage porous carbon fiber membrane with phase-change material, tannin acid and metal nanoenzyme, a dressing with multimodal antibacterial ability was formed.
The dressing has excellent antibacterial properties and the effect of promoting wound healing, can effectively destroy bacterial structure, improve wound healing speed, and is suitable for large-scale production.
Smart Images

Figure CN119465508A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedicine, and particularly relates to a hybrid phase-change porous fiber membrane with enhanced antibacterial properties, and a preparation method and application thereof. Background Art
[0002] The skin is the largest organ in the human body, and its barrier function protects the human body from the invasion of exogenous microorganisms and pathogens. When a wound is infected by bacteria, it is easy to induce an inflammatory response, thereby hindering the basic process of wound healing. Therefore, the effective and safe healing of bacterial-infected wounds is a major clinical challenge. At present, wound dressings are mainly used clinically to promote wound healing. Traditional wound dressings (bandages and gauze, etc.) are prone to tissue adhesion when in contact with the wound for a long time, causing pain and bleeding in the wound when replaced, causing secondary damage, and do not have antibacterial and healing-promoting functions. Therefore, the development of new multifunctional wound dressings has become a research hotspot. With the advancement of nanotechnology and biomaterials science, electrospun fiber dressings have shown broad application prospects in the treatment of bacterial-infected wounds due to their high porosity, high specific surface area, and extracellular matrix (ECM)-like structure.
[0003] Electrospinning is a technology with high parameter controllability, simple process, direct, continuous and efficient preparation of micro / nano fibers, and regulation of their morphology, structure and size. By optimizing the spinning process, porous fibers with higher specific surface area, more active sites and richer pore structure can be prepared, thereby accelerating the diffusion, transmission or conversion of substances, and are widely used in many fields. For example, in the biomedical field, porous nanofibers have good loading and delivery capabilities for substances due to their high specific surface area. They can inactivate bacteria by loading antibacterial agents, and can also load phase change materials and use the photothermal conversion characteristics of porous carbon fibers to achieve light-controlled switch drug release. It is an effective solution for preparing new multifunctional wound dressings.
[0004] At present, some antibacterial therapies have become cutting-edge therapeutic strategies for the treatment of bacterial infections, such as photothermal therapy (PTT), chemodynamic therapy (CDT), photodynamic therapy (PDT), metal ion therapy (MIT), etc. However, due to the different antibacterial principles, single-mode antibacterial therapy has certain limitations in the treatment of infected wounds, so there is an urgent need to develop new wound dressings with multi-mode antibacterial capabilities. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a hybrid phase change porous fiber membrane with enhanced antibacterial properties.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned hybrid phase change porous fiber membrane with enhanced antibacterial properties.
[0007] Another object of the present invention is to provide the use of the hybrid phase change porous fiber membrane with enhanced antibacterial properties in the preparation of infected wound treatment materials.
[0008] The purpose of the present invention is achieved through the following solutions: A hybrid phase-change porous fiber membrane with enhanced antibacterial properties comprises a multi-level porous carbon fiber membrane and a phase-change material, tannic acid (TA), and a metal nanozyme loaded on the multi-level porous carbon fiber membrane.
[0009] The phase change material is a fatty acid phase change material, including at least one of lauric acid, stearic acid, myristic acid, and capric acid, preferably lauric acid.
[0010] The metal nanozyme is a peroxidase-like nanozyme, including at least one of platinum nanoparticles, gold nanorods, and silver nanoparticles, preferably platinum nanoparticles.
[0011] The multi-level porous carbon fiber membrane is prepared by the following steps: (1) Preparation of ZIF-67 nanoparticles: a cobalt salt solution and a dimethylimidazole solution are mixed and stirred and subjected to a coprecipitation reaction to obtain ZIF-67 nanoparticles; (2) Preparation of electrospinning solution: Add ZIF-67 nanoparticles with a particle size of 150 nm into polyacrylonitrile (PAN) solution and stir thoroughly to disperse them completely to form a uniform and stable mixed spinning solution; (3) Electrospinning to prepare precursor composite fibers: electrospinning the polyacrylonitrile / ZIF-67 nanoparticle electrospinning solution obtained in step (2) as a raw material to obtain precursor PAN / ZIF-67 composite fibers; (4) Preparing a carbon fiber membrane by pre-oxidation and calcination: The precursor composite fiber obtained in step (3) is subjected to gradient pre-oxidation and calcination to obtain a multi-level porous carbon fiber membrane.
[0012] The cobalt salt in step (1) is at least one of cobalt nitrate hexahydrate, cobalt acetate, cobalt chloride and cobalt sulfate, preferably cobalt nitrate hexahydrate; the solvent of the cobalt salt solution and the dimethylimidazole solution is at least one of water and methanol, preferably water.
[0013] The concentration of the cobalt salt solution in step (1) is 0.40-0.45 mol / L, preferably 0.41 mol / L; the concentration of the dimethylimidazole solution is 5-6 mol / L, preferably 5.5 mol / L.
[0014] During the mixing and stirring in step (1), the molar ratio of cobalt ions, dimethylimidazole and solvent in the solution is 1:50-55:650-700, preferably 1:53:680.
[0015] The mixing and stirring time in step (1) is 1-4 hours; the stirring speed is 600-1000 rpm.
[0016] The mixing and stirring in step (1) is carried out at a stirring speed of 800 rpm for 2 hours; the coprecipitation reaction is followed by purification, specifically, the reaction solution is centrifuged at 9000 rpm for 10 minutes, repeated 3 times; and then freeze-dried.
[0017] The solvent of the polyacrylonitrile solution in step (2) is at least one of N,N-dimethylformamide, dichloromethane and hexafluoroisopropanol; preferably N,N-dimethylformamide.
[0018] The weight average molecular weight of the polyacrylonitrile in step (2) is 10,000-20,000, preferably 15,000.
[0019] The concentration of the polyacrylonitrile solution in step (2) is 8-12wt%, preferably 10wt%.
[0020] The mass ratio of the polyacrylonitrile to the ZIF-67 nanoparticles in step (2) is 100:50-70.
[0021] The parameters of the electrospinning in step (3) include: an electrostatic field voltage range of 12-20 kV, a spinning receiving spacing of 15-25 cm, a syringe propulsion speed of 0.5-2 mL / h, and a drum speed of 1500-3000 rpm.
[0022] After the electrospinning in step (3), the obtained product is dried, wherein the drying temperature is 40-60° C. and the drying time is 12-24 h.
[0023] The gradient pre-oxidation in step (4) is specifically to oxidize at 180°C, 200°C, 220°C, and 240°C in an air atmosphere for 30-60 min in sequence, then heat up to 250°C and oxidize at this temperature for 1-3 h, and then cool to room temperature to obtain the pre-oxidized composite fiber.
[0024] The calcination in step (4) is specifically to raise the temperature to 800-1000°C at a rate of 5°C / min under an argon atmosphere and calcine at a constant temperature for 2-6 hours to obtain a multi-level porous carbon fiber membrane.
[0025] The preparation method of the above-mentioned enhanced antibacterial hybrid phase change porous fiber membrane includes the following steps: immersing the multi-level porous carbon fiber membrane in a methanol solution containing phase change material, tannic acid, and metal nanoenzymes, and immersing it at room temperature for 12-36 hours to obtain an enhanced antibacterial hybrid phase change porous fiber membrane.
[0026] The molar ratio of the phase change material, tannic acid and metal nanozyme is 4500-5000:50-60:1; preferably 4990:58.8:1.
[0027] The mass ratio of the multi-level porous carbon fiber membrane to tannic acid is 0.12-0.250:2, preferably 0.200:2; The amount of methanol used is such that the concentration of the phase change material in the solution obtained after mixing is 0.4-0.5 mol / L, preferably 0.49 mol / L.
[0028] After the immersion, the hybrid phase change porous fiber membrane is taken out, washed with water for 3 times, and then vacuum dried; wherein the drying temperature is 30-40°C, preferably 37°C; and the drying time is 12-24h, preferably 24h.
[0029] The application of the above-mentioned hybrid phase change porous fiber membrane with enhanced antibacterial properties in the preparation of infected wound treatment materials.
[0030] The application is specifically to cover the infected wound with the hybrid phase change porous fiber membrane, then drip a 100 μM hydrogen peroxide solution to infiltrate the hybrid phase change porous fiber membrane, and then irradiate the hybrid phase change porous fiber membrane with a laser.
[0031] Unless otherwise specified, the temperature in the present invention is assumed to be room temperature.
[0032] The mechanism of the present invention is: The present invention uses a microporous material ZIF (zeolite imidazolate framework) with a highly customized and clear pore structure as a pore-forming template and composites it with polyacrylonitrile (PAN) fiber, and then prepares PAN-based porous carbon fibers through pre-oxidation, high-temperature calcination and other processes. The prepared porous carbon nanofibers have a high specific surface area, rich three-dimensional multi-level porous structure, good photothermal conversion ability, and good drug loading and delivery capabilities, which are conducive to the encapsulation and loading of phase change materials, nanoenzymes, small molecule acids, etc.
[0033] When H2O2 is added and laser irradiated, the PTT antibacterial effect of Pt NPs in the HCF / LA / TA / Pt hybrid phase change porous fiber membrane, the natural antibacterial effect of TA released by LA phase change, the antibacterial effect of Pt NPs themselves, and the antibacterial effect of Pt NPs activated by the weakly acidic environment provided by TA to catalyze H2O2 to generate reactive oxygen species (ROS) jointly show a destructive effect on the bacterial structure and have a high lethality to bacteria.
[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention adopts an electrospinning method to prepare a hybrid phase-change porous fiber membrane with enhanced antibacterial properties. The equipment and process are simple, the repeatability is good, and large-scale production can be carried out.
[0035] 2. The HCF porous fiber membrane obtained by the present invention has a multi-level porous structure and high porosity, and has a good encapsulation effect and a high loading rate for phase change materials, nanoenzymes and tannic acid.
[0036] 3. The HCF / LA / TA / Pt hybrid phase change porous fiber membrane obtained by the present invention has excellent antibacterial properties and wound healing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of ZIF-67 nanoparticles of different particle sizes obtained in Example 1 are shown.
[0038] Figure 2 These are SEM and TEM images of the precursor composite fiber obtained in Example 2 and its corresponding porous fiber membrane.
[0039] Figure 3 Schematic diagram of the preparation process of the hybrid phase change porous fiber membrane with enhanced antibacterial properties in the examples.
[0040] Figure 4 The N2 adsorption-desorption isotherm and BJH pore size distribution curve of the porous fiber membrane obtained in Example 2.
[0041] Figure 5 The hybrid phase change porous fiber membrane obtained in Example 3 and its corresponding SEM and TEM images.
[0042] Figure 6 The hybrid phase change porous fiber membrane obtained in Example 3 is used in antibacterial applications.
[0043] Figure 7 This is the application of the hybrid phase change porous fiber membrane obtained in Example 3 in the treatment of bacterial infected wounds. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0045] Unless otherwise specified, the reagents used in the examples can be purchased from the market.
[0046] Example 1: Preparation of ZIF-67 Nanoparticles First, 1.2 g of cobalt nitrate hexahydrate was weighed and added to 10, 20, and 25 mL of deionized water respectively to dissolve evenly. Then, 18 g of 2-methylimidazole was weighed and added to 40, 80, and 100 mL of deionized water respectively to dissolve evenly by ultrasonication. The two groups of solutions were mixed respectively, stirred at 800 rpm for 2 h, centrifuged at 9000 rpm for 10 min, and washed three times by centrifugation. Then, the solution was freeze-dried at low temperature to obtain ZIF-67 nanoparticles.
[0047] Take a small amount of ZIF-67 nanoparticle powder and stick it on the conductive glue to obtain the scanning electron microscope image of ZIF-67. Figure 1 As shown in the figure, a, d; b, e; c, f are SEM and particle size distribution histograms of ZIF-67 nanoparticles with particle sizes of 150, 300, and 400 nm, respectively. It can be seen from the figure that the three different sizes of ZIF-67 nanoparticles all have a rhombic dodecahedral structure and are evenly distributed. The particle size statistics of ZIF-67 nanoparticles measured by Image J software are 150, 300, and 400 nm, respectively.
[0048] Take a small amount of ZIF-67 ethanol solution, ultrasonically disperse it, and then drop a small amount of the solution onto a copper mesh to prepare a transmission electron microscopy sample. The transmission electron microscopy image of ZIF-67 nanoparticles is shown in Figure 1 As shown, g, h, and i are TEM images of ZIF-67 nanoparticles with particle sizes of 150, 300, and 400 nm, respectively. The ZIF-67 nanoparticles have uniform morphology and present a hexagonal structure, and the particle size is roughly consistent with the SEM results.
[0049] Example 2: Preparation of PAN / ZIF-67 precursor composite fibers with different doping amounts and different particle sizes and porous carbon fibers obtained by calcination 1 g of PAN powder (weight average molecular weight of 15,000) was dissolved in 9 g of N,N-dimethylformamide and stirred until completely dissolved to obtain a 10 wt% PAN spinning solution, to which 30, 50, and 70 wt% of 150 nm ZIF-67 nanoparticles and 70 wt% of 300 and 400 nm ZIF-67 nanoparticles were added respectively to obtain five groups of mixed spinning solutions (where "30, 50, and 70 wt%" refers to the ratio of the mass of ZIF-67 nanoparticles to the mass of PAN). After fully stirring the mixed spinning solutions, electrospinning was carried out with a voltage of 15 kV, a receiving distance of 20 cm, a propulsion flow rate of 1 mL / h, and a drum speed of 2000 rpm to prepare five groups of precursor composite fibers: PAN / 30% ZIF-67 (150 nm), PAN / 50% ZIF-67 (150 nm), PAN / 70% ZIF-67 (150 nm), PAN / 70% ZIF-67 (300 nm), and PAN / 70% ZIF-67 (400 nm). The fibers were dried in a drying oven at 60 °C for 12 h and set aside.
[0050] The five groups of precursor composite fibers were placed in an electric blast drying oven for gradient pre-oxidation, and then oxidized at 180 ℃, 200 ℃, 220 ℃, and 240 ℃ in an air atmosphere for 0.5 h, then heated to 250 ℃ for 1 h, and then slowly cooled to room temperature to obtain pre-oxidized composite fibers. The pre-oxidized composite fibers were folded and placed in a crucible and placed in a tubular electric furnace for carbonization. The temperature was raised to 800 ℃ at a rate of 5 ℃ / min in an argon atmosphere and calcined at a constant temperature for 3 h to prepare five groups of porous carbon fibers: HCF-30% (150 nm), HCF-50% (150 nm), HCF-70% (150 nm), HCF-70% (300 nm), and HCF-70% (400 nm).
[0051] The five groups of precursor composite fibers and their corresponding porous carbon fibers were cut into small pieces and glued to conductive adhesive. After gold spraying, scanning electron microscope images of the five groups of precursor composite fibers and their corresponding porous carbon fibers were obtained. Several fibers from the five groups of porous carbon fibers were placed in double copper meshes to prepare transmission electron microscope samples. The transmission electron microscope images are shown in FIG. Figure 2 shown.
[0052] Figure 2ab; ef; ij; mn; qr are SEM images of PAN / 30% ZIF-67 (150 nm), PAN / 50% ZIF-67 (150 nm), PAN / 70% ZIF-67 (150 nm), PAN / 70% ZIF-67 (300 nm), and PAN / 70% ZIF-67 (400 nm), respectively. The results show that the fiber morphology is uniform and the arrangement is oriented. With the increase of doping concentration, the original composite fiber ( Figure 2 The number of particles on the surface of (a, e, and i) increases, but the distribution of ZIF-67 nanoparticles in the fibers is relatively uniform, with no obvious agglomeration. Figure 2 In the figure, i, m, and q are comparisons of ZIF-67 nanoparticle composite fibers with different particle sizes. The SEM results show that with the increase of particle size, the distribution of ZIF-67 nanoparticles in the fibers becomes uneven, and obvious agglomeration occurs.
[0053] Figure 2 CD, GH, KL, OP, ST are SEM images and TEM images of HCF-30% (150 nm), HCF-50% (150 nm), HCF-70% (150 nm), HCF-70% (300 nm), and HCF-70% (400 nm), respectively. It can be seen from the figure that the carbon fibers of each group after calcination ( Figure 2 The surface pores in (c, g, k) also increase with the increase of ZIF-67 nanoparticle doping amount. TEM results ( Figure 2 d, h, l) also show that the higher the doping amount, the more pores there are inside the fiber and a three-dimensional interconnected network structure is formed. TEM results ( Figure 2 The l, p, t in the figure also show that the internal pores of the carbon fibers with large doping particle sizes are unevenly distributed, and the pores in the HCF-70% (400 nm) fibers are mostly isolated from each other.
[0054] The specific reaction routes of Example 2 and Example 3 are as follows Figure 3 Shown The five groups of porous carbon fibers prepared in Example 2 were subjected to N2 adsorption and desorption tests to study the differences in their internal porous structures. An appropriate amount of porous carbon fibers was placed in a weighed sample tube, placed in a degassing station for heating and vacuum degassing to remove the air and water vapor adsorbed by the sample itself, the dry weight of the fiber sample was weighed and calculated, the sample tube was placed in an analysis station and a filling rod was inserted, and nitrogen adsorption and desorption tests were performed.
[0055] The adsorption-desorption isotherms calculated by the BET model are shown in Figure 4As shown in a, we can see that all five groups of curves have hysteresis loops, which belong to type IV isotherms. Among them, HCF-50% (150 nm) and HCF-70% (150 nm) belong to the H2 type hysteresis loop, with a saturated adsorption platform, which is commonly seen in some three-dimensional mesoporous (2-50 nm) materials; while HCF-70% (300 nm) and HCF-70% (400 nm) belong to the H3 type hysteresis loop, and HCF-30% (150 nm) belongs to the H4 type hysteresis loop. They all have no obvious saturated adsorption platform, indicating that their pore structure is irregular.
[0056] The pore size distribution curve of carbon fiber calculated by BJH method is as follows Figure 4 As shown in (b), it is also consistent with the results calculated by the BET model. The internal pores of the two groups of fibers, HCF-50% (150 nm) and HCF-70% (150 nm), are multi-level porous structures dominated by mesoporous (2-50 nm) structures, while the other three groups have no obvious peaks within the pore size of 100 nm and are irregular macroporous (>50 nm) structures.
[0057] Example 3: Preparation of HCF / LA / TA / Pt hybrid phase change porous fiber membrane The prepared porous carbon fibers were adsorbed with lauric acid, tannic acid and platinum nanoparticles by an impregnation method to prepare a hybrid phase change porous fiber membrane. First, 20 g LA powder, 2 g TA powder and 4 mgPt NPs were placed in a 500 mL beaker, and 200 mL methanol was added to dissolve them evenly to obtain a mixed solution. Secondly, 200 mg HCF-70% (150 nm) porous fibers were weighed and soaked in the above mixed solution and placed on a shaker for 24 h. After the soaking, the hybrid phase change porous fibers were washed with deionized water three times and dried in a vacuum oven at 37 °C for 24 h to obtain a HCF / LA / TA / Pt hybrid phase change porous fiber membrane.
[0058] HCF / LA, HCF / LA / TA, and HCF / LA / Pt were prepared by the same method. HCF / LA is 200 mg HCF-70% (150 nm) loaded with 20 g LA powder; HCF / LA / TA is 200 mg HCF-70% (150 nm) loaded with 20 g LA powder and 2 g TA powder; HCF / LA / Pt is 200 mg HCF-70% (150 nm) loaded with 20 g LA powder and 4 mg PtNPs.
[0059] The hybrid phase change porous fiber membranes of different components were cut into small pieces and glued to the conductive glue. After gold spraying, the scanning electron microscope images of each group of porous fiber membranes were obtained. Several fibers of the hybrid phase change porous fiber membranes of different components were placed in a double copper mesh to prepare transmission electron microscope samples. The transmission electron microscope images are shown in FIG. Figure 5 shown.
[0060] Figure 5 The SEM images and TEM images of four groups of hybrid phase change porous fibers, HCF / LA, HCF / LA / TA, HCF / LA / Pt, and HCF / LA / TA / Pt, show that the fibers still retain a certain orientation structure. Figure 2 The pores on the surface of the original porous carbon fiber HCF-70% (150 nm) are filled after loading their respective components, and bump-like protrusions can be seen on the fiber surface. This is the load whose main component adsorbed by the fiber pores is LA, while the loading content of TA and Pt NPs is low. Therefore, the three groups of fibers loaded with these two components do not show significant differences from the HCF / LA composite fibers in the SEM images.
[0061] The results of TEM are consistent with those of SEM. Figure 2 The TEM image of the original porous carbon fiber HCF-70% (150 nm) shows that the pores inside the fiber are filled with the load, while the TEM images of the two groups of composite fibers hybridized with Pt NPs show small round black dots with a higher contrast than the surrounding area. These are the PtNPs loaded inside the fiber. The TEM image also shows that the loading amount of PtNPs in the fiber is small and sparsely distributed.
[0062] Application Example 1: Antibacterial Effect of HCF / LA / TA / Pt Hybrid Phase Change Porous Fiber Membrane on Escherichia coli and Staphylococcus aureus (1) Preparation of bacterial suspension: Escherichia coli (ATCC25922) and Staphylococcus aureus (ATCC6538) were inoculated into LB liquid medium (Beijing Coolbo Technology Co., Ltd.) and cultured at 37°C for 6-9 h. The bacterial suspension was inoculated onto LB solid medium (purchased from Beijing Coolbo Technology Co., Ltd.) by the plate streak method and cultured inverted at 37°C for 18-24 h. A single colony was picked and placed in LB liquid medium and cultured inverted at 37°C and 100 rpm for 6-9 h to prepare 1.0×10 5 CFU / mL of bacterial suspension.
[0063] (2) 1.5 mg of hybrid phase change composite fibers of different components (HCF / LA group, HCF / LA / TA group, HCF / LA / Pt group and HCF / LA / TA / Pt group) were mixed with 1.5 mL of bacterial solution (1×10 5CFU / mL) for 12 h, and four groups of control experiments were set up according to whether H2O2 was added and whether laser irradiation was used (None, H2O2, Laser, H2O2+Laser, where the H2O2 concentration was 100 μM, the Laser was 1064 nm near-infrared laser, and the Laser irradiation time was 10 min). The bacterial solution after 12 h of co-culture was diluted 10 4 After the number of cells reached 1000 CFU / mL, 50 μL was dropped onto LB solid medium and spread evenly. After culturing at 37°C and 100 rpm for 24 h, the plate was taken out and photographed for counting. Figure 6 shown.
[0064] For comparison, a control group was set up, which was a blank control group with only bacterial solution and no other treatment. 5 CFU / mL bacterial suspension was cultured.
[0065] from Figure 6 It can be seen that there is no significant difference in the colony counts of Escherichia coli and Staphylococcus aureus in the control group under four different conditions. The antibacterial effect of the control fiber did not change significantly after adding H2O2, which indicates that the 100 μM concentration of H2O2 itself has no obvious killing effect on the two bacteria. After 10 minutes of laser irradiation, the colony count of HCF / LA composite fiber decreased, and the HCF / LA / TA composite fiber released more TA due to the photothermal effect, the antibacterial effect was enhanced, and the colony count was further reduced; after adding H2O2 and laser irradiation, the antibacterial effect of HCF / LA / TA / Pt composite fiber reached the best, and no colonies appeared. The high antibacterial activity of HCF / LA / TA / Pt hybrid phase change porous fiber is attributed to the photothermal antibacterial effect of Pt NPs, the natural antibacterial effect of TA released by LA phase change, and the antibacterial effect of Pt NPs activated by the weakly acidic environment provided by TA to catalyze H2O2 to generate ROS.
[0066] Application Example 2: Effect of HCF / LA / TA / Pt hybrid phase change porous fiber membrane on wounds infected with Staphylococcus aureus In this experiment, Staphylococcus aureus ( S. aureus, ATCC6538)-infected rat full-thickness wound defect model was used to evaluate the performance of HCF / LA / TA / Pt hybrid phase change composite fibers in promoting wound healing. The experiment was conducted on SD rats (250-300g, 8 weeks old), and all animal experiments were approved by the Animal Research Committee of South China Agricultural University. According to different experimental conditions, all rats were randomly divided into five groups, namely control group (treated with commercial dressing Tegaderm film (3MHealthCare, USA)), HCF / LA / TA / Pt group, HCF / LA / TA / Pt + H2O2 group, HCF / LA / TA / Pt + Laser group, and HCF / LA / TA / Pt + H2O2+ Laser group, in which the H2O2 concentration was 100 μM, and the group without H2O2 was replaced with an equal amount of PBS. The Laser was a 1064 nm near-infrared laser, and the Laser irradiation time was 10 min. There were 3 rats in each group. After the rats were anesthetized, a circular wound with a diameter of 15 mm was cut on their backs, and the wound was treated with S. aureus The rats were infected with bacterial suspension and recorded as day 1. The wound dressings were changed and laser irradiation was performed on days 1, 3, 5, and 7. The wound healing status of rats in each group was recorded by taking photos every other day.
[0067] from Figure 7 It can be seen that on the 3rd day, the wound healing effect of the HCF / LA / TA / Pt + H2O2+ Laser treatment group was significantly better than that of the other four groups. On the 7th day, the wound areas of the HCF / LA / TA / Pt + H2O2, HCF / LA / TA / Pt + Laser, and HCF / LA / TA / Pt+ H2O2+ Laser groups were significantly reduced, and the best healing effect was in the HCF / LA / TA / Pt +H2O2+ Laser treatment group. By the 14th day, the wounds of the HCF / LA / TA / Pt+ H2O2+ Laser treatment group had basically healed. Therefore, under the irradiation of H2O2 and Laser, the HCF / LA / TA / Pt hybrid phase change porous fiber membrane has good performance in promoting wound healing.
[0068] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A hybrid phase change porous fiber membrane with enhanced antibacterial properties, characterized in that: It includes a multi-level porous carbon fiber membrane and a phase change material, tannic acid and metal nanozyme loaded on the multi-level porous carbon fiber membrane.
2. The hybrid phase change porous fiber membrane with enhanced antibacterial properties according to claim 1, characterized in that: The phase change material is a fatty acid phase change material, including at least one of lauric acid, stearic acid, myristic acid, and capric acid; The metal nanozyme is a peroxidase-like nanozyme, including at least one of platinum nanoparticles, gold nanorods, and silver nanoparticles.
3. The hybrid phase change porous fiber membrane with enhanced antibacterial properties according to claim 1, characterized in that: The multi-level porous carbon fiber membrane is prepared by the following steps: (1) Preparation of ZIF-67 nanoparticles: a cobalt salt solution and a dimethylimidazole solution are mixed and stirred and subjected to a coprecipitation reaction to obtain ZIF-67 nanoparticles; (2) Preparation of electrospinning solution: Add ZIF-67 nanoparticles with a particle size of 150 nm into the polyacrylonitrile solution and stir thoroughly to disperse them completely to form a uniform and stable mixed spinning solution; (3) Electrospinning to prepare precursor composite fibers: electrospinning the polyacrylonitrile / ZIF-67 nanoparticle electrospinning solution obtained in step (2) as a raw material to obtain precursor PAN / ZIF-67 composite fibers; (4) Preparing a carbon fiber membrane by pre-oxidation and calcination: The precursor composite fiber obtained in step (3) is subjected to gradient pre-oxidation and calcination to obtain a multi-level porous carbon fiber membrane.
4. The hybrid phase change porous fiber membrane with enhanced antibacterial properties according to claim 3, characterized in that: The cobalt salt in step (1) is at least one of cobalt nitrate hexahydrate, cobalt acetate, cobalt chloride and cobalt sulfate; the solvent of the cobalt salt solution and the dimethylimidazole solution is at least one of water and methanol; The concentration of the cobalt salt solution in step (1) is 0.40-0.45 mol / L; the concentration of the dimethylimidazole solution is 5-6 mol / L; During the mixing and stirring in step (1), the molar ratio of cobalt ions, dimethylimidazole and solvent in the solution is 1:50-55:650-700; The mixing and stirring time in step (1) is 1-4 hours; the stirring speed is 600-1000 rpm.
5. The hybrid phase change porous fiber membrane with enhanced antibacterial properties according to claim 3, characterized in that: The solvent of the polyacrylonitrile solution in step (2) is at least one of N,N-dimethylformamide, dichloromethane and hexafluoroisopropanol; The weight average molecular weight of the polyacrylonitrile in step (2) is 10000-20000; The concentration of the polyacrylonitrile solution in step (2) is 8-12wt%; The mass ratio of the polyacrylonitrile to the ZIF-67 nanoparticles in step (2) is 100:50-70.
6. The hybrid phase change porous fiber membrane with enhanced antibacterial properties according to claim 3, characterized in that: The electrospinning parameters of step (3) include: an electrostatic field voltage range of 12-20 kV, a spinning receiving spacing of 15-25 cm, a syringe propulsion speed of 0.5-2 mL / h, and a drum speed of 1500-3000 rpm; The gradient pre-oxidation in step (4) is specifically to oxidize at 180°C, 200°C, 220°C, and 240°C in an air atmosphere for 30-60 min, then heat up to 250°C for 1-3 h, and then cool to room temperature to obtain the pre-oxidized composite fiber; The calcination in step (4) is specifically to raise the temperature to 800-1000°C at a rate of 5°C / min under an argon atmosphere and calcine at a constant temperature for 2-6 hours to obtain a multi-level porous carbon fiber membrane.
7. The method for preparing the hybrid phase change porous fiber membrane with enhanced antibacterial properties according to any one of claims 1 to 6, characterized in that: The following steps are involved: The multi-level porous carbon fiber membrane is immersed in a methanol solution containing phase change material, tannic acid, and metal nanoenzyme at room temperature for 12-36 hours to obtain a hybrid phase change porous fiber membrane with enhanced antibacterial properties.
8. The method for preparing the hybrid phase change porous fiber membrane with enhanced antibacterial properties according to claim 7, characterized in that: The molar ratio of the phase change material, tannic acid and metal nanozyme is 4500-5000:50-60:1; The mass ratio of the multi-level porous carbon fiber membrane to tannic acid is 0.12-0.250:2; The amount of methanol used is such that the concentration of the phase change material in the solution obtained after mixing is 0.4-0.5 mol / L.
9. Use of the hybrid phase change porous fiber membrane with enhanced antibacterial properties according to any one of claims 1 to 6 in the preparation of materials for treating infected wounds.
10. The use of the hybrid phase change porous fiber membrane with enhanced antibacterial properties according to claim 9 in the preparation of infected wound treatment materials, characterized in that: The application is specifically to cover the infected wound with the hybrid phase change porous fiber membrane, then drip a 100 μM hydrogen peroxide solution to infiltrate the hybrid phase change porous fiber membrane, and then irradiate the hybrid phase change porous fiber membrane with a laser.
Citation Information
Patent Citations
ZIF-8 / poly(vinyl alcohol) (PVA) composite nanofiber membrane as well as preparation method and application thereof
CN105951304A
Silicon dioxide nanofiber membrane loaded with ZIF-8 and used for purifying air
CN107503044A
One-step method for preparing hierarchical pore nanofiber membrane for air purification
CN109695096A
Silver nanowire-based polarizing film and preparation method and application thereof
CN114325915A
Nanometer enzyme for enhancing antibiosis through chemodynamic therapy and preparation method and application of nanometer enzyme composite fiber membrane
CN118542961A